PENGARUH BUDAYA KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI BUKIT INDAH - I Made Chandra Mandira; Ni Made Ayu Anggreni (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2023)
This study aims to determine the influence of work culture, work discipline, job satisfaction in part and at the same time on employee performance. The sample for this study was 32 people. Informal analytical techniques use multiple linear regression analysis. According to the research results, work culture, work discipline and job satisfaction have a significant influence on employee performance. The degree of influence of the independent variables on employee performance is 66.1.   Keywords: Company Culture, Work Discipline, Job Satisfaction, Employee Performance.